Diabetic Cheiroarthropathy: A Case Report and Review of the Literature - Rabia Cherqaoui; Sheldon McKenzie; Gail Nunlee-Bland (Case Reports in Endocrinology)
Diabetes mellitus is associated with a wide variety of rheumatologic manifestations which can significantly affect a patient's quality of life. One of these manifestations includes diabetic cheiroarthropathy (DCA) which affects the hands. We review a case of a 28-year-old female patient with type 1 diabetes mellitus who was diagnosed with DCA after complaining of limited movements of all joints in her hands and tightening of the skin. We examine how the diagnosis was made, the treatment administered, and the successful clinical outcome. Clinicians should be able to identify and treat this affliction. The diagnosis is mainly clinical. It is imperative to remember that the presence of DCA carries with it a significant relationship with microvascular disease.